2022
DOI: 10.1088/1757-899x/1247/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors affecting the energy consumption of an EV vehicle - a literature study

Abstract: One of the most requested information about an electric vehicle is its energy consumption. This parameter is particularly important for electric vehicles users who drive them in real conditions. This paper aims to conduct literature research on the factors affecting the energy consumption of a vehicle. The article contains a set of information concerning how the temperature, traffic conditions, or properties of an electric vehicle translate into energy consumption. The results of studies presented in various p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Consisting of p pairs of poles and the rotor rotating in synchronism with the rotating stator field at the angular speed ω, then the speed of the motor Ω can be written as follows: (11) Depending on the electrical model, we could write:…”
Section: The Brushless Enginementioning
confidence: 99%
See 1 more Smart Citation
“…Consisting of p pairs of poles and the rotor rotating in synchronism with the rotating stator field at the angular speed ω, then the speed of the motor Ω can be written as follows: (11) Depending on the electrical model, we could write:…”
Section: The Brushless Enginementioning
confidence: 99%
“…The driving environment such as freezing temperatures and strong winds drastically reduce vehicle's range. In [11] Skuza and Jurecki show that negative temperatures can reduce EV's range by up to 37%, while at a temperature of 40°C, it is possible to extend the range by about 2%.…”
Section: Introductionmentioning
confidence: 99%
“…By meticulously scrutinizing these drive cycles, we gain vital insights into the precise moments when an electric vehicle transitions between different driving phases-uniform velocity, acceleration, and deceleration. It is in these transitions that power consumption fluctuates, significantly influencing the driving range and overall efficiency of EVs [4] [5].One of the central themes of this research is the estimation of critical parameters essential for enhancing EV performance [6]. We delve into the intricacies of battery capacity, energy consumption rates, and powertrain efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In [ 25 ], the researchers emphasized the use of energy consumption as a criterion to compare EVs. A heat map and causal association analysis revealed that there was no correlation between energy consumption and charging speed, but there was a significant correlation with range and maximum velocity.…”
Section: Introductionmentioning
confidence: 99%